Effects of Electropulsing Treatment on the Microstructure and Mechanical Property of M2 High-speed Steel - Zhang Jiatao, Liu Zhaohua, Ye Lirun (Teshugang)
Using conventional heat treatment combined with electrical pulse treatment （abbreviated EPT） ，the M2 high-speed steel was processed and the microstructure was observed using microscope， SEM and EBSD， the bending resistance of the specimen was tested. The results showed that the prior austenite grains （abbreviated PAGs） size of sample pretreated at 1 200 ℃ was about 24 μm， the austenite grain size was significantly refined after EPT， the grain size was refined to 4.8 μm while quenching at 1 140 ℃.The maximum bending strength of the refined M2 high-speed steel reached to 3 799 MPa， which was 39% higher than quenching at 1 180 ℃ of conventional heat treatment（abbreviated CHT）.Compared with the size change of austenite grain of M2 high-speed steel during the CHT ， it can be found that the grain refinement effect produced by EPT was not due to cyclic quenching， but it should be due to the high overheat generated by rapid heating and the influence of non-thermal effect on the nucleation rate.